The Effect Of Return On Investment, Price Earning Ratio, And Dividend Policy On The Stock Price Of Pt. Bank Mega Tbk 2013-2024 Period - David, David; Astuti, Eni Puji (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine the Effect of Return On Investment (ROI), Price Earning Ratio (PER) and Dividend Policy on Stock Prices at PT. Bank Mega Tbk for the 2013-2024 Period. The independent variables used in this study are Return On Investment (X1), Price Earning Ratio (X2) and Dividend Policy (X3), while the dependent variable used in this study is Stock Price (Y). The data used are secondary data from the annual financial statements for the 2013-2024 period. This type of research uses a quantitative method with an associative descriptive approach. The data analysis techniques used in this study are descriptive statistical analysis, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), multiple regression analysis, quantitative tests (correlation test and determination test) and hypothesis testing (t-test and f-test) with the help of SPSS 27 software (Statistical Product and Service Solution 27). The results of the study indicate that Return on Investment (ROI) partially influences stock prices, Price Earnings Ratio (PER) partially influences stock prices, and Dividend Policy partially does not. Simultaneously, Return on Investment (ROI), Price Earnings Ratio (PER), and Dividend Policy all influence stock prices.